No Difference in Ligamentous Strain or Knee Kinematics Between Rectangular or Cylindrical Femoral Tunnels During Anatomic ACL Reconstruction With a Bone–Patellar Tendon–Bone Graft. Issue 6 (8th June 2021) - Burkhart, Timothy A.; Hoshino, Takashi; Batty, Lachlan M.; Blokker, Alexandra; Roessler, Philip P.; Sidhu, Rajeshwar; Drangova, Maria; Holdsworth, David W.; Petrov, Ivailo; Degen, Ryan; Getgood, Alan M.
Background: As our understanding of anterior cruciate ligament (ACL) anatomy has evolved, surgical techniques to better replicate the native anatomy have been developed. It has been proposed that the introduction of a rectangular socket ACL reconstruction to replace a ribbon-shaped ACL has the potential to improve knee kinematics after ACL reconstruction. Purpose: To compare a rectangular femoral tunnel (RFT) with a cylindrical femoral tunnel (CFT) in terms of replicating native ACL strain and knee kinematics in a time-zero biomechanical anatomic ACL reconstruction model using a bone–patellar tendon–bone (BTB) graft. Study Design: Controlled laboratory study. Methods: In total, 16 fresh-frozen, human cadaveric knees were tested in a 5 degrees of freedom, computed tomography–compatible joint motion simulator. Knees were tested with the ACL intact before randomization to RFT or CFT ACL reconstruction using a BTB graft. An anterior translation load and an internal rotation moment were each applied at 0°, 30°, 60°, and 90° of knee flexion. A simulated pivot shift was performed at 0° and 30° of knee flexion. Ligament strain and knee kinematics were assessed using computed tomography facilitated by insertion of zirconium dioxide beads placed within the substance of the native ACL and BTB grafts. Results: For the ACL-intact state, there were no differences between groups in terms of ACL strain or knee kinematics. After ACL reconstruction, there were no differences in ACL graft strain when comparing the RFT and CFT groups. At 60° of knee flexion with anterior translation load, there was significantly reduced strain in the reconstructed state ([mean ±standard deviation] CFT native, 2.82 ± 3.54 vs CFT reconstructed, 0.95 ± 2.69; RFT native, 2.77 ± 1.71 vs RFT reconstructed, 1.40 ± 1.76) independent of the femoral tunnel type. In terms of knee kinematics, there were no differences when comparing the RFT and CFT groups. Both reconstructive techniques were mostly effective in restoring native knee kinematics and ligament strain patterns as compared with the native ACL. Conclusion: In the time-zero biomechanical environment, similar graft strains and knee kinematics were achieved using RFT and CFT BTB ACL reconstructions. Both techniques appeared to be equally effective in restoring kinematics associated with the native ACL state. Clinical Relevance: These data suggest that in terms of knee kinematics and graft strain, there is no benefit in performing the more technically challenging RFT as compared with a CFT BTB ACL reconstruction.